Clinical significance of the combination of preoperative SUVmax and CEA in patients with clinical stage IA lung adenocarcinoma. Issue 18 (12th August 2022) - Hashinokuchi, Asato; Haratake, Naoki; Takenaka, Tomoyoshi; Matsudo, Kyoto; Nagano, Taichi; Watanabe, Kenji; Kosai, Keisuke; Oku, Yuka; Ono, Yuki; Takamori, Shinkichi; Kohno, Mikihiro; Baba, Shingo; et al.
Abstract: Background: Preoperative maximum standardized uptake value (SUVmax) of 2‐[18F]‐fluoro‐2‐deoxy‐D‐glucose positron emission tomography and serum carcinoembryonic antigen (CEA) have been reported as prognostic factors for lung adenocarcinoma. However, the significance of combined SUVmax and CEA in early‐stage lung adenocarcinoma is not well known. Methods: We retrospectively evaluated the relationship between the combination of SUVmax and CEA and the prognosis of 410 patients with clinical stage IA lung adenocarcinoma who underwent resection. The cutoff values for SUVmax and CEA were determined by receiver operating characteristic curve analysis, and patients were categorized into high SC (SUVmax and CEA) group (SUVmax ≥2.96 and CEA ≥5.3), moderate SC group (either SUVmax <2.96 and CEA ≥5.3 or SUVmax ≥2.96 and CEA <5.3) and low SC group (SUVmax <2.96 and CEA <5.3). Results: Kaplan–Meier curve analysis showed that patients with clinical stage IA lung adenocarcinoma in the high SC group had significantly shorter overall survival (OS) and recurrence‐free survival (RFS) than the other groups ( p = 0.011 and p < 0.0001, respectively). Multivariate analysis showed that high SC was an independent prognostic factor of OS ( p = 0.029) and RFS ( p < 0.0001). Conclusions: High values of SUVmax and CEA were associated with poor OS and RFS in patients with stage IA lung adenocarcinoma. Simultaneous evaluation of SUVmax and CEA may be an effective prognostic marker to determine the optimal treatment strategy of early‐stage lung adenocarcinoma. Abstract : We retrospectively evaluated the relationship between the combination of SUVmax and CEA and the prognosis of 410 patients with clinical stage IA lung adenocarcinoma who underwent resection.